Optimisation of Irrigation Parameters and Response of Water Use Efficiency for Greenhouse Common Bean in Cold and Arid Regions of China - Lijuan Jia; Yinkun Li; Xiaoming Wei; Guiyan Wang; Minjie Duan; Jizhong Zhang; Wenzhong Guo (Irrigation and Drainage, 2026)
Efficient irrigation management is essential for improving the yield and water use efficiency (WUE) of greenhouse vegetables in the cold and arid region of northwestern Hebei Province, China. To determine the optimal irrigation coefficient ( K p ) for common beans, a 2‐year (2022–2023) greenhouse experiment was conducted using five irrigation treatments on the basis of cumulative pan evaporation ( E p ): I1 (0.3 E p ), I2 (0.5 E p ), I3 (0.7 E p ), I4 (0.9 E p ) and I5 (1.1 E p ). Results showed that treatment I3 achieved the highest yield and WUE, increasing by 8% and 66%, respectively, compared with I5. In addition to its superior agronomic performance, the I3 treatment also improved fruit nutritional quality, as indicated by higher vitamin C content, lower nitrate accumulation and greater single‐fruit weight than the other treatments. A comprehensive evaluation using entropy weight‐grey relational analysis ranked I3 as the most favourable treatment, followed by I4, I2, I1 and I5. The yield exhibited a significant quadratic relationship with K p , and the fitted model predicted a theoretical maximum yield of 34.65 t/ha at K p = 0.755, closely corresponding to the I3 treatment. Consequently, a K p value of approximately 0.755 is recommended as the irrigation control parameter for maximizing both yield and WUE in greenhouse‐grown common beans under local conditions.